ENERGY-EFFICIENT CLUSTER BASED ARCHITECTURE DESIGN FOR WIRELESS SENSOR NETWORKS - KHAN, ASFANDYAR (2011)
Sensor networks are unlike other forms of networks in a variety of ways with respect to their various functionalities in the sense that they are severely hampered by inadequate local resources such as battery power, storage and the dependability of each node. These networks usually consist of cheap, unreliable nodes. Due to these properties, the efficient collaboration among individual nodes which is essential for the successful completion of the overall network task might be lacking. Moreover, efficient collaboration is necessary for providing services such as information processing, message transmission, maximizing network lifetime and for the reduction of propagation delay. There are several network design parameters which have a tremendous impact on the lifetime of the network; among these parameters are latency, routing and energy efficient techniques. These are the most important ones because in some critical application areas a quick response may be necessary and an accurate form of the data must be received by the end user.